Variability Of Some Selection Parameters of Karakol Sheep in the Conditions of the Sandy Desert (Texas Journal of Agriculture and Biological Sciences, 2022)
The article describes the results of the study of the variation of some selection parameters of black Karakol sheep depending on the mating types.